A comprehensive approach to assess marine macro litter pollution and its impacts on corals in the Bangka Strait, North Sulawesi, Indonesia. (February 2022) - Mueller, Jasmin S.; Bill, Nicolas; Reinach, Marco S.; Lasut, Markus T.; Freund, Holger; Schupp, Peter J.
Abstract: This is a comprehensive study showing the marine anthropogenic litter pollution within North Sulawesi, Indonesia. From an area of 2972 m 2 that encompassed five sparsely populated locations, a total of 9421 litter items weighing 137 kg were collected. One location (Talisei North) contributed 50% of all collected litter items. Plastic litter always dominated with 96–99%. Litter was unevenly distributed across investigated areas reaching from the upper beach (3.6–30.1 items/m 2 ) to the reef slope (0–0.03 items/m 2 ). Litter composition and daily accumulation showed spatial-temporal dynamics, with upper beach areas displaying the overall highest accumulation rates. Reef micro-habitats were differently affected, with the reef moat and reef flat showing the highest litter concentrations, although litter amounts were much lower compared to the corresponding beaches. Branching corals, especially Porites cylindrica, were most affected by litter entanglement. Field experiments with P. cylindrica showed that attached plastic induced bleaching, necrosis, and algal overgrowth within five months. Highlights: Beach environments of North Sulawesi were much more polluted than their associated fringing reefs. 96-99% of all marine anthropogenic litter items were composed of plastic, mainly lightweight single-use plastics. Changed weather conditions influenced pollution levels & daily accumulation was higher during the rainy than the dry season. Reef moats and reef flats were the main underwater sinks for marine litter. Branched scleractinian were mostly impacted & P. cylindrica had irreversible damage after 5 months of plastic exposure.